49. ASSESSMENT OF RELAPSE PREVENTION ADHERENCE IN SCHIZOPHRENIA BY PRIMARY CAREGIVERS IN NAM DINH PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objectives: to evaluate the knowledge and practice of primary caregivers in preventing relapse of patients with schizophrenia and identify related factors in Nam Dinh province. Methods: cross-sectional description. Study location: Nam Dinh Province, Vietnam. Study period: From June to December 2024.Results: 52.2% of primary caregivers had good and good knowledge, and 85.7% fully complied with regular check-ups; compliance also provided adequate nutrition for 92.7%; compliance with personal hygiene management of 91.9%, compliance with communication rehabilitation for 79.7%; compliance with medication was 63.6%, compliance with occupational rehabilitation was 8.3%; factors about family economy and knowledge are the main factors related to caregivers' practice with p < 0.05.Conclusion: the knowledge and practice of schizophrenia are still limited, it is necessary to take measures to improve knowledge and support families of people with schizophrenia in the treatment and prevention of the disease.
Keywords: Care for schizophrenic patients.